POTENSI TUMBUHAN SUMBER PAKAN LEBAH MADU HUTAN (Apis dorsata) DI KAWASAN TAMAN NASIONAL LORE LINDU WILAYAH DESA KAMARORA - Patabang, Irma; Rukmi, Rukmi; Mallombasang, Sri Ningsih; Rosyid, Abdul (Jurnal Warta Rimba, 2021)
Lore Lindu National Park is one of the conservation areas that has the potential for forest honey bees (Apis dorsata) forage. This study aims to identify the types of food sources for forest honey bees (Apis dorsata) and calculate the Importance Value Index (IVI) of plant species. The research was carried out for 2 months, namely from September to October 2020, in the Lore Lindu National Park, in the area of Kamarora B Village, Nokilalaki District, Sigi Regency. Field data collection was carried out by conducting a vegetation inventory using the method of multiple plots which were placed intentionally (purposive sampling) as many as 30 plots. The analysis used in this research is vegetation analysis. The results showed that the total number of plant species was 575 individuals consisting of 84 types of plants with 59 families. The number of potential food sources for forest honey bees (Apis dorsata) is 50 species consisting of 42 families or 42% of the total number of plants obtained. The results of the calculation of the highest Importance Value Index (IVI) are owned by the level of enau (Arenga pinnata) trees, namely 47.20%, the level of cacao plants (Theobroma cacao) with 65.17%, the level of saplings is cassava (Manihot esculenta) 45.66% then the level of seedlings and understorey is enau (Arenga pinnata) 51.97%.Keywords: Potential forage, Forest Honey Bees, Lore Lindu National Park